1990
DOI: 10.1172/jci114917
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic studies of radioiodinated serum amyloid P component in normal subjects and patients with systemic amyloidosis.

Abstract: Abstract"25I-Serum amyloid P component (SAP), injected intravenously into 10 normal subjects, remained predominantly intravascular with mean (SD) T112 (half time) in plasma of 24.5 (5.9) h. The fractional catabolic rate of 68 (19)% of the plasma pool per day was more rapid than other reported human plasma proteins. All radioactivity was excreted in the urine by 14 d. In 16 patients with monoclonal gammopathy or chronic inflammatory diseases, but without amyloidosis, 1251-SAP metabolism was normal. However, amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0
1

Year Published

1993
1993
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(51 citation statements)
references
References 40 publications
3
47
0
1
Order By: Relevance
“…Doxycycline-induced overexpression of SAA is thus totally independent of inflammation. Doubletransgenic mice exposed to drinking water containing 2 mg/mL doxycycline developed major systemic amyloid deposits after a median of 5 wk (range, 4-16 wk) as shown by massive whole body retention of i.v.-administered 125 I-human SAP ( 125 I-hSAP), a validated, specific, quantitative in vivo tracer for systemic amyloid deposits in mice (14,15) and humans (16)(17)(18). Heavy AA amyloid deposits were confirmed histologically in the spleen and liver, correlating closely with the major organ localization of 125 I-hSAP.…”
Section: Resultsmentioning
confidence: 99%
“…Doxycycline-induced overexpression of SAA is thus totally independent of inflammation. Doubletransgenic mice exposed to drinking water containing 2 mg/mL doxycycline developed major systemic amyloid deposits after a median of 5 wk (range, 4-16 wk) as shown by massive whole body retention of i.v.-administered 125 I-human SAP ( 125 I-hSAP), a validated, specific, quantitative in vivo tracer for systemic amyloid deposits in mice (14,15) and humans (16)(17)(18). Heavy AA amyloid deposits were confirmed histologically in the spleen and liver, correlating closely with the major organ localization of 125 I-hSAP.…”
Section: Resultsmentioning
confidence: 99%
“…The most exquisitely sensitive test for protein integrity, namely its turnover after intravenous injection in vivo, is absolutely normal for SAP isolated from serum heated in that way (17).…”
Section: Discussionmentioning
confidence: 99%
“…However, before the widespread recognition of the association between cerebral amyloidosis and Alzheimer's disease, systemic amyloidosis was of no interest to pharmaceutical companies. Our subsequent clinical work with radiolabelled tracer SAP, coupled with precise characterization of SAP from blood and tissues, demonstrated that SAP in amyloid is indistinguishable from its plasma precursor, that SAP persists in the deposits for prolonged periods, and that SAP is not catabolized at all in the deposits but only when it reenters the blood and is then taken up by hepatocytes (Hawkins et al 1990b;). These observations supported the concept that SAP may provide a normal, autologous protein coat masking the abnormal amyloid ¢brils from the scavenging processes that usually so e¤ciently clear the tissues of abnormal material.…”
Section: (C) Inhibition Of ¢Brillogenesismentioning
confidence: 99%